Whose nature? Whose rights? Criminalization of Social Protest in a globalizing world - Gustavo Rojas Paez (Oñati Socio-Legal Series)
This introductory essay provides a reflection on the historical configuration of law and its relationship with nature's exploitation. In doing so, it seeks to highlight the epistemic foundations surrounding the criminalization of social protest in today’s globalized world. The essay revolves around the question of why the law has historically disregarded both environmental and social harm. Finally, the discussion concludes by suggesting a paradigm shift in the fields of criminology and legal theory.